Feature detectors and motion detection in video processing - Dey, Nilanjan 1984-; Ashour, Amira 1975-; Patra, Prasenjit Kr. 1987- (Advances in multimedia and interactive technologies book series, 2017)
This book explores innovative methods and approaches to analyzing and retrieving video images, featuring empirical research and significant frameworks regarding feature detectors and descriptor algorithms